PENGARUH JAM KERJA TERHADAP PENINGKATAN PENDAPATAN PEMULUNG DI KECAMATAN TAMPAN KOTA PEKANBARU PROVINSI RIAU - Herman, herman (Sekolah Tinggi Ilmu Ekonomi Riau, 2016)
The purpose of this study is to determine how much influence the working hours to increased revenue scavengers in Kecamatan Tampan Kota Pekanbaru. The population in this study are scavengers numbering 39 person. Mechanical sampling is dine by using a nonprobability sampling. The data analysis is done by using validity, reliability, simple linier regression, uji_t, and the coefficient of determination. The test are conducted in order to determine the relationship between independent variables and the dependent variabel.Based on the research that significantly influence the working hours increased revenue scavengers in Kecamatan Tampan Kota Pekanbaru. It can be see significant value for 0.000 is smaller than 0.05. the amount of influence of independent variabeles on the dependent variable was 30.4 persent while the remaining 69.6 persent is influenced by other variables not examinedThe conclusion from this study is that the hypothesis in the sudy is to reject H0